Intuition in judgment and decision making - Plessner, Henning (Psychology Press, 2009)
The nature of intuition -- Learning and intuition -- Emotion and intuition -- The assets and deficits of intuition
Includes bibliographical references and index
Keywords: Entscheidungsfindung; Intuition